Of macrophages and red blood cells; a complex love story - de Back, Djuna Z.; Kostova, Elena B.; van Kraaij, Marian; van den Berg, Timo K.; Van Bruggen, Robin (Frontiers in Physiology, 2014)
Macrophages tightly control the production and clearance of red blood cells (RBC). During steady state haematopoiesis, approximately 1010 red blood cells are produced per hour within erythroblastic islands in humans. In these erythroblastic islands, resident bone marrow macrophages provide erythroblasts with interactions that are essential for erythroid development. New evidence suggests that not only under homeostasis but also under stress conditions, macrophages play an important role in promoting erythropoiesis. Once RBC have matured, these cells remain in circulation for about 120 days. At the end of their life span, RBC are cleared by macrophages residing in the spleen and the liver. Current theories about the removal of senescent RBC and the essential role of macrophages will be discussed as well as the role of macrophages in facilitating the removal of damaged cellular content from the RBC. In this review we will provide an overview on the role of macrophages in the regulation of RBC production, maintenance and clearance. In addition, we will discuss the interactions between these two cell types during transfer of immune complexes and pathogens from RBC to macrophages.